Traditional Baduanjin exercise through the eyes of patients with chronic heart failure: A qualitative content analysis study - Chen, Xiankun; Jiang, Wei; Salazar, Mariano; Zhu, Huiying; Wen, Zehuai; Chen, Xixi; Lundborg, Cecilia Stålsby (Frontiers in Cardiovascular Medicine, 2023)
Objective: Baduanjin (eight silken movements) is a traditional Chinese exercise that can be used as cardiac rehabilitation therapy for patients with chronic heart failure especially when other forms of rehabilitation are scarce or unaffordable. This study explores the experiences of Chinese patients with chronic heart failure who undertook Baduanjin exercise at home as part of a pilot trial in Guangzhou, China. Methods: Seven qualitative interviews were conducted with participants who participated in the intervention arm of a pilot randomized controlled trial (n=8). A semi-structured interview guide with open-ended, and follow-up questions was used to collect the data. Interviews were audio recorded , transcribed verbatim and analyzed using content analysis. Results: Participants’ experiences of doing Baduanjin were classified into three categories (1) improving practice (2) factors facilitating good exercise adherence, and (3) feeling good. Participants reported that the exercises were easy but the correct execution and coordination of the mind, the movements, and breathing in Baduanjin can only be achieved through practice. In addition, the perceived training benefits were the predominant motivation for patients to keep practicing. Finally, trust in Baduanjin, personal attitudes towards health, flexibility in practice times, as well as social support helped the participants to achieve good adherence to home-based training. Conclusions: Findings from this study suggest that Baduanjin has the potential to become a cardiac rehabilitation exercise modality for patients with chronic heart failure in China, especially in a home-based setting.